Experimental study on the effect of vortex cavitation in scaled-up diesel injector nozzles and spray characteristics - Cao, Tianyi; He, Zhixia; Zhou, Han; Guan, Wei; Zhang, Liang; Wang, Qian (Experimental thermal and fluid science, 2020)
•A flow visualization experiment with a 10 scaled-up transparent nozzle was done.•Hollow spray was observed for the first time.•The pressure fluctuation of four kinds of vortex cavitation was studied. The working stability, service life of the injector, spray atomization and its subsequent mixture combustion are subject to significant influence from the cavitating flow in diesel nozzles. In this paper, the vortex cavitation characteristics in diesel nozzles and its effects on spray characteristics were investigated by performing visualization experiments in scaled-up optical nozzles. A pressure fluctuation test system was constructed for the effect of vortex cavitation occurring in holes on pressure fluctuations. It was concluded that vortex cavitation is one of the most significant influencing factors in pressure fluctuations for the injection system. Furthermore, the inception and the development of vortex cavitation were discussed in detail.